Protective security management in critical sectors of Malaysian government agencies - Mohd Saiful Hisham bin Md. Salleh (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
The crime, opportunities for rule breaking violations, weakness or gap in a security program include structural, procedural, policy, electronic, human and other elements would provide opportunities to attack government assets and critical information. Statistics and case study shows that the vulnerable area need to improve soon. Thus, the government must do a systematic approach used to assess a government department's security posture, analyze the effectiveness of the existing security program and tools, and identify security weaknesses. To implement protective security standards, agencies are required to clearly identify internal security governance structures and delineate responsibilities. The follow up and follow through movement across level of public servant are most required. There are many benefits an organization will enjoy when it makes those improvements, not the least of which is the budget justification for creating a security awareness program that help will boost security effectiveness overall. Organizations that have achieved a high level of security effectiveness are better able to identify major security breaches, secure confidential information, limit physical access to government assets, and achieve compliance with legal and self-regulatory frameworks. Organizations that maximize the efficacy of their security awareness programs stand to benefit not only from better incident prevention, but many other benefits as well, including improved reputation and customer loyalty.